Structural analysis of proteins by isotope-edited FTIR spectroscopy. Issue 1 (2010) - Tatulian, Suren A.
Abstract : Structure determination of multidomain proteins or protein–membrane complexes is one of the most challenging tasks in modern structural biology. High-resolution techniques, like NMR or X-ray crystallography, are limited to molecules of moderate size or those that can be crystallized easily. Both methods encounter serious technical obstacles in structural analysis of protein–membrane systems. This work describes an emerging biophysical technique that combines segmental isotope labeling of proteins with Fourier transform infrared (FTIR) spectroscopy, which provides site-specific structural information on proteins and allows structural characterization of protein–membrane complexes. Labeling of a segment of the protein with 13 C results in infrared spectral resolution of the labeled and unlabeled parts and thus allows identification of structural changes in specific domains/segments of the protein that accompany functional transitions. Segmental isotope labeling also allows determination of the precise configuration of protein–membrane complexes by polarized attenuated total reflection FTIR (ATR–FTIR) spectroscopy. These new developments offer solutions to functionally important site-specific structural changes in proteins and protein–membrane complexes that are hard to approach using conventional methods.